Tunisia : Staff Report for the Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that despite a contraction of agricultural production, Tunisia's GDP grew by 5 percent in 1998. Gross fixed capital formation (27.5 percent of GDP), notably in Tunisia's traditional and new export sectors, was the most dynamic component of aggregate demand. The external current account deficit widened only slightly to 3.4 percent of GDP owing to a commensurate increase in the saving rate. Growth of exports of goods and services slowed primarily owing to a decline in sales of crude oil and food products.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet